The component of ecological approach to apple plantations chemical protection - Gunchak, M.V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The main factor for decreasing of danger of apple garden chemical protection from pests and diseases is a preparations’ selection. The more dangerous insecticides with degree of danger 3 expediently to replace by moderately dangerous with degree of danger 4. The fungicides with degree of danger 6 are the little dangerous.